ANALYSIS OF EXISTING THREATS AND VULNERABILITIES IN COMPUTER NETWORKS (Academicia Globe: Inderscience Research, 2022)
This article will focus on possible threats and vulnerabilities in computer networks. When comparing the internal and external vulnerabilities of the network, the shortcomings, vulnerabilities and threats contained in the protocols are caused precisely by which perimeter attacks are made. At the end of the article, suggestions and recommendations were made against these vulnerabilities.